The Effect of Perceived Self-efficacy and Its Antecedents on Perceived Employees Performance of Thailand Automobile Assembly Industry - Tangchongrat, Thiraphon; Meechaisue, Prayong; Chinuntdej, Norapol (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This article aimed to study 1) the impact of perceived organizational support on work motivation, self-efficacy, and its antecedents on perceived employee’s performance; and 2) the causal influence of self-efficacy and its antecedents on perceived employee’s performance in the automobile assembly industry in Thailand by using integrated research, quantitative research, and a questionnaire. The sample of 450 employees at the automotive assembly industry operating level was carried out by multistage sampling. Using descriptive statistics and confirmatory factor analysis. For the qualitative research, an interview tool was used. The key informants were 5 executives of an automobile assembly company. The data was analyzed using content analysis principles before being written up as a descriptive description. The research results were found as follows: 1) the causal model was harmoniously consistent with the empirical data, with values 2/df = 1.09, P = 0.18862 and RMSEA = 0.015, explaining the variance of perceived employee’s performance by 77%; work motivation had the highest positive impact on perceived employee’s performance, and the perceived organizational support variable had a negative impact on 2 variables, namely self-efficacy and perceived employee’s performance; and 2) The qualitative research findings reasoned against the negative assumptions that this may be due to the unclear understanding of employees because the Kaizen principle emphasizes on-site workers as the ones who know best. By providing support through small group activities that result from the informal gathering of employees in the same department to continuously do small improvement activities together.